Tajemnica Ducha Świętego w katechezie sakramentu bierzmowania - Dziekoński, Stanisław (Studia Pastoralne, 2008)
Preparing for the Sacrament of Confirmation is one of the more important issues of contemporary catechesis. In Poland many interesting programs directly concerning this preparation have been published. These differ between them on the level of substance and methods. Whatever a program is to be accepted, it must be remembered that the central theme of these encounters should be the mystery of the Holy Spirit. This mystery can be fathomed from different sides and in many ways, but always with the use of biblical sources, patristic sources, the teaching of the Church and the rich theological reflection that is available. In the context of Confirmation especially important are the issues concerning the presence and action of the Holy Spirit at the beginning of the Church and in full Christian initiation; the gifts and fruits of the Holy Spirit; life in the power of the Holy Spirit in the contemporary world. These issues have been developed in this article, addressed above all to those responsible for the catechesis of those preparing for the Sacrament of Confirmation.